2022
DOI: 10.1186/s12882-021-02646-x
|View full text |Cite|
|
Sign up to set email alerts
|

Chlorhexidine – a commonly used but often neglected culprit of dialysis associated anaphylactic reactions (case report)

Abstract: Background Hemodialysis-associated anaphylactic reactions are rare and frequently complex in nature due to the sheer number of possible culprit agents. Unfortunately, dialysis is often unavoidable or strictly essential for life-saving solute clearance or fluid removal in patients with end stage kidney failure and those with severe acute kidney injury. It is of utmost importance that the culprit agent is identified and avoided to allow continuation of dialysis treatment as needed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…1 Allergic contact dermatitis is more common with chlorhexidine than with other antiseptics. 2 Although several studies have reported chlorhexidine sensitization in health care workers, few have examined the prevalence in other groups frequently exposed to chlorhexidine, such as dialysis patients. 3 Allergic contact dermatitis is a delayed T-cell-mediated hypersensitivity reaction that occurs in those with repeated allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Allergic contact dermatitis is more common with chlorhexidine than with other antiseptics. 2 Although several studies have reported chlorhexidine sensitization in health care workers, few have examined the prevalence in other groups frequently exposed to chlorhexidine, such as dialysis patients. 3 Allergic contact dermatitis is a delayed T-cell-mediated hypersensitivity reaction that occurs in those with repeated allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…2 Hemodialysis patients are relatively anergic, which may reduce the symptoms of contact sensitization and result in isolated pruritus without other eczematous changes. 2 Although initial irritation is often deemed insignificant, it may foreshadow more severe reactions on continued exposure because the risk of sensitization grows with repeated exposure and higher concentrations. 4 In fact, perioperative anaphylaxis due to chlorhexidine has been documented in a patient with unknown chlorhexidine sensitization that occurred years before the anaphylactic event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correction to: BMC Nephrology (2022) 23:18 https://doi.org/10.1186/s12882-021-02646-x Following publication of the original article [1], the authors identified an error in the author name of Yi DA.…”
Section: Open Accessmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Yi DA.…”
mentioning
confidence: 99%